Quick slide test for estimating the pathogenicity of staphylococci: the comparison of coagulase activity with clumping in citrated normal human plasma - Akman, Muvaffak; Çobanoğlu, Muzaffer (The Turkish Journal of Pediatrics, 1961)
Coagulase positive staphylococci are rapidly clumped in normal citrated human plasma (or in its dilutions) when an attempt is made to suspend them in tubes or on slides. Coagulase negative strains give quite homogeneous suspensions. The difference between positive and negative strains is very clear.Experiments made by other authors, as well as our tests, have shown that the parallelism between coagulase production and slide clumping tests is evident and the rate of correlation is rather high. It was always above 97 per cent and was 100 per cent when pure cultures of staphylococci were used.Since coagulase production is believed to be the most important criterion for pathogenicity, the slide test can be used in estimating the pathogenicity of staphylococci and gives satisfactory results within 20 seconds. The slide test is a cheap, time saving, dependable test.In the text, the technic of our tests and results and also the correlation between the type of pigment and of coagulase production is given.